Malaysia simulation auditory map for blind children education / Noramilia Had - Had, Noramilia (2008)
A map is difficult to access by blind people because it is a type of picture. Blind people only can access this picture by using the auditory that used hearing and tactile image that used haptic sensory to touch the border of the image. An individual is considered visually impaired when, despite any optical or surgical corrections, there is a severe loss of visual acuity or loss of visual field .The degree of visual impairment varies from total blindness to low vision .This study is conducted to explore the possibility of using computer assisted systems to assist blind children to read Malaysia maps. The objective of this study is to identify the needs of blind children in reading and the major objective is to design the Malaysia Simulation Auditory map for blind children education. The blind children can access with their own to read Malaysia map in interactive ways without normal people guided. With this Malaysia map information the blind children reading process is become more interesting and they also can improve their general knowledge about states in Malaysia. . This auditory is presenting in Malay language because it easy to understand by the blind children and this auditory map will be used in Malaysia. The Malaysia simulation auditory map is used an auditory that contains speech and non speech to present the Malaysia states information.